DON'T BE REASSURED BY AN UNDETECTABLE SERUM HIV VIRAL LOAD. Issue 10 (9th September 2014) - Shanmugarajah, Priya; Weerasinghe, Kalani; Warren, Daniel; Ford, Helen
Abstract : The immunologically privileged CNS can act as a reservoir for HIV-1 replication and mutation. Antiretrovirals can differ in their CNS penetration. Patients on HAART with serologically undetectable HIV-1 viral load can present with new neurological symptoms. A 48 year-old right-handed woman with a 4 year history of HIV, presented with focal motor and secondary generalised seizures, a week after alteration of established HAART. She had previous VZV encephalitis and HIV-associated neurocognitive disorder. The CD4 count was 212 with undetectable serum HIV-1 viral load. However, HIV-1 viral copies were detectable in the CSF. Extensive investigations excluded opportunistic infection and neoplasm. MRI demonstrated a progressive leucoencephalopathy; CT-angiography revealing intracranial angiitis with multifocal arterial aneurysm formation. She was treated with high-dose IV steroids and reducing oral steroids. We reinstated nevirapine and zidovudine was added to the high CNS penetrative HAART regime. HIV-1 viral copies were undetectable on repeat CSF. She had no further seizures but she remained dependent for ADLs. We postulate that the acute intracranial angiitis was secondary to neuro-IRIS following a change in the HAART treatment. This case illustrates the importance of recognizing the CNS as a HIV reservoir and the possibility of neuro-IRIS occurring at later stages of the disease.